Fra apokalyptik til science fiction. Jakob Balling in memoriam - Jensen, Søren (Dansk Teologisk Tidsskrift, 2012)
In his book Poeterne som kirkelærere (The Poets as Theologians) Jakob Balling compares Dante’s Divine Comedy with Milton’s Paradise Lost. He discusses similarities and differences between the two poems and places them in a literary tradition that combines theology and poetry, a relationship that has had a decisive influence on the development of literature in Europe. The present article expands this perspective both backwards and forwards in time by including a discussion of the interrelationship between fi ction and religious message in Jewish apocalyptic, using the Apocalypse of Abraham and C.S. Lewis’ modern science fiction novel Out of the Silent Planet as examples. The article’s discussion of the relationship between theology and fi ction raises the question of the apocalyptic as genre. Moreover, the demonstration of the fi ctional tendency in the apocalyptic is used to support and supplement the traditional description of genre.